2020
DOI: 10.1111/eva.13081
|View full text |Cite
|
Sign up to set email alerts
|

Growing in the city: Urban evolutionary ecology of avian growth rates

Abstract: Introduction Rapid environmental change driven by urbanization offers a unique insight into the adaptive potential of urban‐dwelling organisms. Urban‐driven phenotypic differentiation is increasingly often demonstrated, but the impact of urbanization (here modelled as the percentage of impervious surface (ISA) around each nestbox) on offspring developmental rates and subsequent survival remains poorly understood. Furthermore, the role of selection on urban‐driven phenotypic divergence was rarely investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 109 publications
0
50
0
Order By: Relevance
“…Abundant prey species associated with urban environments such as brown rats (Rattus norvegicus), rock pigeons (Columba livia), and house mice (Mus musculus) could potentially be driving predation rates and protein (i.e. nitrogen) consumption, at least for mammalian and avian predators (Corsini et al;Newsome et al, 2010;Mccabe et al, 2018;Scholz et al, 2020). Our findings are contrary to an emerging hypothesis of relaxed predation phenomenon in urban areas, described by a meta-analysis of 25 studies that found predation rates on bird nests were reduced in urban areas (Eötvös et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Abundant prey species associated with urban environments such as brown rats (Rattus norvegicus), rock pigeons (Columba livia), and house mice (Mus musculus) could potentially be driving predation rates and protein (i.e. nitrogen) consumption, at least for mammalian and avian predators (Corsini et al;Newsome et al, 2010;Mccabe et al, 2018;Scholz et al, 2020). Our findings are contrary to an emerging hypothesis of relaxed predation phenomenon in urban areas, described by a meta-analysis of 25 studies that found predation rates on bird nests were reduced in urban areas (Eötvös et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Great tits are hole-nesting passerine birds known to occupy a wide range of habitats, from primary forests (Tomiałojć and Wesołowski, 2004) to urban city centres (Corsini et al, 2020). In this species, the nesting environment is an important driver that shapes gut microbiota during early development (Teyssier et al, 2018a), making the great tit an ideal subject to study microbial changes across an urban mosaic.…”
Section: Study Sitementioning
confidence: 99%
“…We included the following sampling sites: a natural forest (c. 10 km from the city borders and approximately 20 km from the city centre), a peri-urban village bordering a natural forest, 2 residential areas, 2 urban woodlands, a large urban park and an office area. These sites are presented in greater detail by Corsini et al (2019Corsini et al ( , 2020. In adsdition to the 8 sites described above, woodcrete nest boxes (Schwegler, Germany, Type 1B) and natural cavities were also monitored at a 9th site: the Bielany Forest, which is a unique forest remnant of the Masovian Primeval forest (and retains some of its features); this forest has an area of ca.…”
Section: Study Sitementioning
confidence: 99%
“…In this study, we used genome-wide and epigenome-wide sequencing approaches to compare genetic and epigenetic responses among three pairs of great tit Parus major populations in urban and forest habitats. At the European level, population monitoring of Great tits revealed parallel phenotypic shifts in city birds compared to their forest conspecifics, with in particular smaller and lighter urban birds laying earlier and smaller clutches (33)(34)(35)(36). We investigated both average genomic (SNPs) and epigenomic (CpG methylation) differentiation and we searched for particular genomic footprints of divergent selection as well as differentially methylated regions, between forest and urban populations.…”
Section: Introductionmentioning
confidence: 99%